(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In structural analysis, the term ’frame’ typically refers to a robust structure comprising various elements such as slabs, beams, columns, and footings. These components are cast together to create a monolithic construction, effectively functioning as a single integral unit. The frame is subject to various forces, which are transferred through its different components. Additionally, changes in facility usage or the introduction of additional live loads can exert further stresses on the structure. Consequently, it is imperative that the elements of the frame possess sufficient strength to withstand these loads. In this study, we focus on the development of approaches for strengthening and retrofitting concrete beams using structural steel elements. Specifically, our investigation involves the analysis of beams under different load combinations to enhance their integrity performance. To achieve this, angles and steel plates are utilized for reinforcement. We conduct numerical analysis through finite element modeling using ANSYS Workbench. Multiple beam models are created within the ANSYS platform, allowing us to study and compare various outcomes, including total deformation. This comprehensive approach aims to contribute to the advancement of methods for enhancing the structural resilience of concrete beams in real-world applications.